2021
DOI: 10.1016/j.molmet.2021.101298
|View full text |Cite
|
Sign up to set email alerts
|

Role of hypothalamic de novo ceramides synthesis in obesity and associated metabolic disorders

Abstract: Background Sphingolipid-mediated signalling pathways are described as important players in the normal functioning of neurons and nonneuronal cells in the central nervous system (CNS). Scope of review This review aims to show role of de novo ceramide synthesis in the CNS in controling key physiological processes, including food intake, energy expenditure, and thermogenesis. The corollary is a condition that leads to a dysfunction in ceramide me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 96 publications
0
11
0
Order By: Relevance
“…We speculate that decreased body weight gain in CerS6 KO mice might be due to reduced food consumption and an increased rate of energy expenditure, which agrees with previous studies. Accrual of hypothalamic ceramides stimulates orexigenic pathways, dysregulates energy balance, and further perturbs glucose homeostasis in mice models [25]. In addition, central administration of a cell-permeable C 6:0 -ceramide analogue to the hypothalamus increases hypothalamic C 16:0 -ceramides, and subsequently increases body weight, which might emphasize the pathological role of C 16:0 -ceramides in obesity [26].…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that decreased body weight gain in CerS6 KO mice might be due to reduced food consumption and an increased rate of energy expenditure, which agrees with previous studies. Accrual of hypothalamic ceramides stimulates orexigenic pathways, dysregulates energy balance, and further perturbs glucose homeostasis in mice models [25]. In addition, central administration of a cell-permeable C 6:0 -ceramide analogue to the hypothalamus increases hypothalamic C 16:0 -ceramides, and subsequently increases body weight, which might emphasize the pathological role of C 16:0 -ceramides in obesity [26].…”
Section: Discussionmentioning
confidence: 99%
“…Those findings show that leptin impacts on ceramide metabolism via malonyl‐CoA and CPT1C, and that ceramide de novo biosynthesis acts downstream of both malonyl‐CoA and CPT1C in regulating food intake and neuropeptide expression. Subsequent studies have also confirmed that dysregulation of hypothalamic de novo ceramide synthesis is a key starting point for central insulin resistance, endoplasmic reticulum stress, inflammation, and, ultimately, obesity 14,31 …”
Section: Hypothalamic Cpt1c and The Ampk‐acetyl‐coa Carboxylase (Acc)...mentioning
confidence: 92%
“…Lipid metabolism within the hypothalamus participates in this process and is a key molecular mechanism in controlling energy balance to counteract nutrient surplus 9,11,12 . There is strong evidence that a disturbance in hypothalamic lipid sensing may be partly responsible for a disrupted energy balance and the development of obesity and insulin resistance 13,14 . In fact, fatty acid (FA) sensing in hypothalamic neurons, via accumulation of long‐chain FAs or FA intermediaries, acts as a satiety signal to decrease food intake and promote energy expenditure 11,15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive ceramides can be produced in three ways ( 6 ). First, the de novo pathway produces 3-keto-dihydrosphingosine by condensation of serine and palmitate catalyzed by serine palmityl transferase (SPT) ( 19 ). Next, sphinganine is N-acylated by six distinct ceramide synthases (CerSs) to form various dihydroceramides.…”
Section: Biosynthesis and Degradation Of Ceramidesmentioning
confidence: 99%